2013
DOI: 10.1002/jssc.201201060
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bisphenol A in thermal printing papers treated by alkaline aqueous solution using the combination of single‐drop microextraction and HPLC

Abstract: A method for the quantitative determination of bisphenol A in thermal printing paper was developed and validated. Bisphenol A was extracted from the paper samples using 2% NaOH solution, then the extracted analyte was enriched using single-drop microextraction followed by HPLC analysis. Several parameters relating to the single-drop microextraction efficiency including extraction solvent, extraction temperature and time, stirring rate, and pH of donor phase were studied and optimized. Spiked recovery of bisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Bisphenol‐contaminated paper can be observed in food packaging to kitchen towels. Printing inks are another probable source of contamination (Gao et al., 2013; Sanchis et al., 2017). The scenario can be understood from analysis where the detected concentration of BPA in virgin PET polymer was remarkably lower (25–432 ng/g) than in recycled material (394–10,120 ng/g) (Dreolin et al., 2019).…”
Section: Regulations and Reported Concentrations In Food Packaging: P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphenol‐contaminated paper can be observed in food packaging to kitchen towels. Printing inks are another probable source of contamination (Gao et al., 2013; Sanchis et al., 2017). The scenario can be understood from analysis where the detected concentration of BPA in virgin PET polymer was remarkably lower (25–432 ng/g) than in recycled material (394–10,120 ng/g) (Dreolin et al., 2019).…”
Section: Regulations and Reported Concentrations In Food Packaging: P...mentioning
confidence: 99%
“…Bisphenols are also considered endocrine modulators (Gallart-Ayala et al, 2013). Several studies have demonstrated that BPA at very low doses (ng/L or mg/L) disrupts hormone action and modifies testosterone synthesis (Gao et al, 2013). Míguez et al (2012) reported that BADGE and BFDGE are tumorigenic and mutagenic.…”
Section: Toxicological Aspects Of Emcs and Human Health Impactsmentioning
confidence: 99%
“…Gao and co-researchers demonstrated single drop microextraction (SDME) coupled with HPLC to determine BPA in thermal printing papers in 2013 [8]. Although the SDME is sensitive due to the extractant in a droplet, the slow kinetics of extraction and instability of the drop cause a longer equilibrium time and higher uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…BPA is frequently quantified by gas chromatography coupled with mass spectrometry (GC/MS) [14][15][16][17][18], highperformance liquid chromatography (HPLC) [19][20][21], and liquid chromatography coupled with mass spectrometry (LC/MS or LC/MS/MS) [16,[22][23][24]. These methods allow high sensitivity and specificity but are labor intensive, expensive, and time consuming because of their complex pretreatment steps.…”
Section: Introductionmentioning
confidence: 99%